KONSEP PERBUATAN DAN TANGGUNG JAWAB INDIVIDU DALAM AL-QURâAN - Irawan, Bambang (LP2M IAIN Mataram, 2012)
The existence and purpose of human creation comprises individual responsibility in all aspects of life. The purpose and responsibility indicated the human functions that make its existence become meaningful. This concept is already contained in the Qurâan in many verses and context, but has not been specifically revealed. This study discusses human activity as it explained in the Qurâan. The method used is the library research, where the al-Quran as the main document. In the implementation, the author focused on verses that explicitly show the conception of human deeds and accountability, more patterned on scientific thematic interpretation. Responsibility in the Qurâan is grouped in two categories: First, individual responsibility against him personally, and second, human responsibility to others and the environment (social) in which he lived. The existence of such responsibilities is as a consequence of the âfreedomâ of man in actualizing its potential to do good and evil